(untitled) (Olhar de Professor, 2019)
This study had as objective to analyze the contribution of the Internship in Teaching in Child Education of the Full Degree in Pedagogy of a Federal Public University for the constitution of the teaching of graduates of the course. In the theoretical structuring of this work, the various authors who based their study, we highlight: Cerisara (1999); Lima (2011); Pimenta (2012); Perrenoud (2002); Roldão (2007) and the legal documents as: Law of Guidelines and Bases of National Education (1996); Federal Constitution (1988); Law nº 11.788 / 2008 and the Pedagogical Project of said course (2007). The analysis of the data showed that the Teaching Internship in Early Childhood Education contributed to the teaching of the students of the course, and that we can not neglect the impact that the lack of efficient follow-up during the Internship can cause in the future professional life of the students. students.